Introgression of Sub1 QTL (Submergence tolerant QTL) into the elite rice variety Jaya by Marker Assisted Backcross Breeding - Arya, K. V.; Shylaraj, K.S. (Journal of Tropical Agriculture, 2019)
Rice (Oryza sativa L.) is the most important staple food crop of Asia. Submergence is the third important abiotic stress affecting rice crop in coastal ecosystems of Kerala due to heavy showers of South-West monsoon. The most viable solution to overcome this problem is to introgress submergence tolerant gene into high yielding elite rice varieties. Hence, the present study was undertaken to introgress submergence tolerant gene (Sub1 gene) into the elite rice variety Jaya through Marker Assisted Backcross Breeding (MABB). Polymorphism assay using 625 SSR markers could select two polymorphic foreground markers, seven polymorphic recombinant markers and 76 polymorphic genome wide markers. The genotypic selection of heterozygous plants was made in F1 and in each backcross generation and in selfed progeny homozygous plants were selected using the selected foreground and recombinant markers. The Sub1 region of the selected BC2F2 progeny ranged from 0.5-5.6 mb and had ≥ 85% homozygosity to that of recurrent parent. These selected progeny were screened for submergence tolerance in vitro and scored according to SES by IRRI which showed similar score to that of the donor parent. Our work could introgress the abiotic stress submergence tolerance controlled by Sub1 gene into the popular rice variety Jaya. The developed abiotic stress tolerant rice lines are under field evaluation and can be cultivated profitably in the coastal ecosystem where flood is the major constraint limiting rice production.